Firm Size and Innovation in the Service Sector - David Audretsch; Marian Hafenstein; Alexander S. Kritikos; Alexander Schiersch (Institute of Labor Economics (IZA), 2018)
A rich literature links knowledge inputs with innovative outputs. However, most of what is known is restricted to manufacturing. This paper analyzes whether the three aspects involving innovative activity - R&D; innovative output; and productivity - hold for knowledge intensive services. Combining the models of Crepon et al. (1998) and of Ackerberg et al. (2015), allows for causal interpretation of the relationship between innovation output and labor productivity. We find that knowledge intensive services benefit from innovation activities in the sense that these activities causally increase their labor productivity. Moreover, the firm size advantage found for manufacturing in previous studies nearly disappears for knowledge intensive services.
Keywords: L25; L60; L80; O31; O33; 330; MSMEs; R&D; service sector; innovation; productivity; entrepreneurship